KAJIAN SEBARAN SALINITAS DENGAN MODEL HEC-RAS DI DAERAH IRIGASI TAMBAK SEI TERAS KALIMANTAN TENGAH - Hermawanto, Hanny Adityanta (JURNAL SUMBER DAYA AIR, 2023)
This study aims to evaluate the distribution of salinity with a mathematical model to enhance advanced aquaculture cultivation. The Sei Teras Fishpond Irrigation Area is one of the aquaculture development areas of the food security program (Food Estate) influenced by tides. Currently, the technology used is simple, and the availability of seeds and feeds depends on nature. The water quality parameters with a specific threshold are needed as an advanced aquaculture requirement to achieve the production level. Vannamei shrimp, as a development commodity, requires a salinity concentration of 15-25 ppt for optimal growth. This study will evaluate the potential of salinity from alternative schemes of introducing gates and normalization against existing conditions using the HEC-RAS program. This program can resolve water quality models with a hydrodynamic simulation procedure through a series of mathematical equations. The simulation results show that the availability of salinity in the two tidal cycles of the spring tide and neap tide could fulfill around 86.7% for 15 days. The normalization has no significant impact on the availability of salinity against existing conditions. The gate influences the longitudinal distribution pattern of salinity. The salinity value above 19 ppt could reach the upstream of the canal up to ± 7 km, while the existing condition could only reach ± 4 km. Therefore, the expected potential of salinity could be achieved.Keywords:       salinity, model simulation, distribution, an alternative scheme